Variability and synchronism of leaf appearance and leaf elongation rates of eleven contrasting rice genotypes - Egle, Rohilyn B.; Domingo, Abigail J.; Bueno, Crisanta; Laurena, Antonio, C.; Aguilar, Edna A.; Santa Cruz, Pompe; Clerget, Benoit (Scientific Research Publishing, Inc., 2015)
Leaf appearance and leaf elongation rates in rice play an essential role in determining the development of the plants’ architecture which affects their adaptability to varying environments. This study aimed to characterize the rates of leaf appearance and elongation on all leaves of the main culms of rice plants for 11 contrasting varieties and to determine if the decrease in the leaf appearance rate was related to a simultaneous decrease in the rate of leaf elongation. Forty four 13-L pots were sown with one plant from one genotype and laid out in 4 randomized complete blocks. The experiment, conducted inside a greenhouse, was repeated twice. The increase in length of the leaves expanding on the main stems was monitored daily until flag leaf. Data were used to estimate the rates of leaf appearance and leaf elongation. Significant variability in the rate of leaf appearance, rate of leaf elongation, and leaf length was found across varieties. The kinetics of leaf appearance had linear phases intermediated by a curvilinear phase, without sharp changes in the phyllochron duration. Maximal leaf elongation rate (LER) of all genotypes (except for one) increased linearly with leaf rank until it reached its maximum value at leaf 8 to 10 (11 - 12 for Azucena) where it stabilized before decreasing linearly with leaf rank for the last leaves. Finally, both rates of leaf appearance and leaf elongation evolved with time more smoothly than expected so no sharp decrease in LER occurred at the time of the decrease in leaf appearance rate of the last leaves. However, the trilinear model fits the data well enough to remain useful in efficiently comparing the leaf appearance kinetics of contrasting varieties